Penyuluhan Metode Restorative Justice dalam Penanganan Prilaku Bullying Di Sekolah - Fuqoha Fuqoha; Hasuri Hasuri; Sasmia Sasmia; Sasmita Sasmita (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2022)
The activity was motivated by the many reports of bullying cases carried out between students and teachers and students in the school. The school should be a safe and comfortable place for students to study. So that the behavior of students who cross the line and lead to acts against the law in the form of bullying is very worrying. This concern is very justified considering the negative impact caused by physical, verbal, psychological and virtual bullying on social media. Therefore, legal counseling is needed regarding the dangers and legal threats to the behavior of acts of bullying and the handling of acts of bullying using restorative justice methods. This activity is carried out using a participatory learning and action model through lectures, discussions, accompanied by actions against bullying behavior. The results of this activity indicate that there are similarities in the goals and expectations of the school as the purpose of this activity regarding education and handling of bullying behavior in schools. Schools want the settlement of cases in schools to be avoided from legal threats by replacing using a restorative approach as the school's function is to educate children.